Diseño de un sistema para reciclar botellas de vidrio en vasos personalizados (2021)
The general objective of this project is Design a system for recycling glass bottles and reuse them as glasses, their added value being reduce the impact that solid waste has on the environment. It is proposed to reuse the glass from the single-use bottles, designing innovative glasses and exclusive. For the design of the machine, it was established a methodology that determines the characteristics of the common bottles found on the market, design the mechanical part of the cutting machine, polished and decorated, design the electrical connections and machine control using a turning arm with hardwired logic. As a final product, it will be delivered the design of the system to recycle bottles, as well as the general plans and a three-dimensional image to show its design. Not included construction or implementation